FAKTOR RISIKO KEJADIAN PENYAKIT JANTUNG KORONER DI POLIKLINIK RSUD SEKARWANGI SUKABUMI PERIODE TAHUN 2021 - Zurriyani Zurriyani; Alyaa Hanifatur Rifdah (Jurnal Sains Riset, 2021)
Coronary heart disease (CHD) is disosder of heart function caused by lack of blood in the heart muscle due to narrowing of coronary arteries. In Indonesia, according to the 2019 PERKI data, the incidence of CHD is the main cause of all deaths in Indonesia, which is 26.4%. This research is descriptive analytical research with cross sectional approach. Samples were taken by consecutive sampling technique amounted to 143 respondents. The research instrument used medical records and questionnaires. Data were analyzed by univariate, bivariate, and multivariate using SPSS. After the data were analyzed, there was a risk relationship with CHD and it was proven to have an effect on the incidence of CHD with the results of the test p 0.05 as follows: age p = 0.040, gender p = 0.000, family history p = 0.047, dyslipidemia p = 0.003, hypertension p=0.014, diabetes mellitus p=0.000, obesity p=0.001, and smoking p=0.032. And what is stronger on the incidence of CHD after being tested simultaneously with p value 0.05, namely gender, p value 0.000 and hypertension 0.001.Keywords: Coronary Heart Disease, Risk Factors, Sukabumi